2017
DOI: 10.1159/000477580
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Training Program Involving Body Cooling on Physical and Cognitive Capacities and Quality of Life in Multiple Sclerosis Patients: A Pilot Study

Abstract: Objective: Two methods using exercise and body cooling could influence the well-being of patients with multiple sclerosis (PwMS). The aim of this study was to determine whether wearing a cooling vest during a physical training program could increase the cognitive and physical capacities and quality of life in PwMS. Methods: Eighteen PwMS (49.6 ± 8 years; Expanded Disability Status Score 5.0 ± 1.0) were randomly assigned to a cooling or control group. PwMS underwent a 7-week physical training program. In the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…used in the interventions. In line with our results, the studies that found improvements in quality of life used intensity of resistance training similar to ours (moderate-to-high; 60–85% 1-RM) 11 12 32 34 . However, the two studies that did not observe a change in quality of life when using lower intensities.…”
Section: Discussionsupporting
confidence: 91%
“…used in the interventions. In line with our results, the studies that found improvements in quality of life used intensity of resistance training similar to ours (moderate-to-high; 60–85% 1-RM) 11 12 32 34 . However, the two studies that did not observe a change in quality of life when using lower intensities.…”
Section: Discussionsupporting
confidence: 91%
“…In the study by Miller et al, after ten sessions of WBC (one exposure per day at −110 • C or lower), patients reported improvements in functional status and feeling of fatigue [61]. Lowering the body temperature with a cooling garment also seems to have a similar positive influence on fatigue [62,63]. Even a single session with a Rehband cooling garment caused many positive changes for MS patients, including subjective improvements in fatigue [64].…”
Section: Physical Agentsmentioning
confidence: 99%
“…Even a single session with a Rehband cooling garment caused many positive changes for MS patients, including subjective improvements in fatigue [64]. The authors of the above-mentioned articles did not report any side effects for the applied treatments [61][62][63][64]. Patients were excluded from the whole-body cryotherapy study if they had any of the following contraindications: antihypertensive or vasoactive medications or diuretics within the previous month; or any other significant medical diagnoses, including thyroid, hypothalamic or cardiovascular disease, circulatory or breathing insufficiency, clotting, embolisms, inflammation of blood vessels, open wounds, ulcers, serious cognitive disturbances, fever, addictions, claustrophobia, or over-sensitivity to cold [61].…”
Section: Physical Agentsmentioning
confidence: 99%
“…Wearing a cooling vest during submaximal exercise under humid temperate conditions ( ≈ 22 °C, ≈ 80 % relative humidity) improves thermal comfort by reducing the perceptions of temperature and humidity and by enhancing a general sense of well-being. The use of such garments should therefore be considered in the context of physical exercise (sport and occupational activities) but also in the context of pathologies, e. g. for multiple sclerosis patients [64]. Regarding physiological responses, this personnel-cooling vest seems to reduce the trunk temperature during exercise and recovery and to allow greater cerebral perfusion and a faster heart rate recovery.…”
Section: Resultsmentioning
confidence: 99%